Pengaruh Hard Skill Dan Soft Skill Terhadap Kinerja Pegawai Dinas Kependudukan Dan Pencatatan Sipil Kabupaten Majene - Muh Fachrul Hidayat; Akbar Azis; Wahdaniah Wahdaniah; Arlistria Muthmainna (Fakultas Ekonomi Universitas Indonesia Timur, 2022)
This study aims to determine the effect of hard skills and soft skills on employee performance at the Department of Population and Civil Registration of Majene Regency. This type of research is quantitative research that uses data collection methods by distributing questionnaires to all civil servants in the Department of Population and Civil Registration of Majene Regency, as many as 30 people. The population of this study were employees at the Department of Population and Civil Registration of Majene Regency, which were 76 people. The sampling method in the study was carried out by purposive sampling technique and obtained 30 respondents who were civil servants as the sample. The hypotheses in this study include: Hard Skills affect Employee Performance, Soft Skills affect Employee Performance, Hard Skills and Soft Skills jointly affect Employee Performance. The results of this study are Hard Skills have a positive and significant effect on employee performance, Soft Skills have a positive and significant effect on employee performance, Hard Skills and Soft Skills jointly affect the performance of the Majene Regency Population and Civil Registration Service employees. So it can be concluded that Hard Skills and Soft Skills can affect employee performance